ALK-positive cancer: still a growing entity. (February 2014) - Gorczyński, Adam; Prełowska, Monika; Adam, Patrick; Czapiewski, Piotr; Biernat, Wojciech
ABSTRACT: Since the discovery of ALK-positive anaplastic large-cell lymphoma in 1994 many other types of tumors showing ALK expression were disclosed. They form a heterogeneous group, including lung, renal and soft tissue tumors. The biological function of ALK, its role in carcinogenesis and impact exerted on the clinical outcome have been studied by many research groups. New drugs specifically dedicated for ALK inhibition, for example, crizotinib, have been synthesized and have become a viable treatment option for ALK-positive lung adenocarcinoma, and potentially for other ALK-positive cancers. This review summarizes the current state of knowledge concerning ALK-positive neoplasms, focusing on the clinical aspects of the subject.